Prevalence and concordance of interpersonal violence reports from intimate partners: findings from the Pacific Islands Families Study. Issue 7 (13th June 2007) - Schluter, Philip J; Paterson, Janis; Feehan, Michael
Abstract : Background: Intimate partner violence (IPV) is an increasingly significant public health issue. Few studies investigate both partners' reports of such violence. Aim: To determine the prevalence of IPV perpetration and victimisation and the concordance of both partners' reports of that violence in a representative sample of Pacific couples using a standardised measure. Methods: A cohort of Pacific infants born during 2000 in Auckland, New Zealand, was followed. At 24-months postpartum, home interviews were conducted separately for mothers and fathers, and experience of IPV within the last 12 months was measured using the Conflict Tactic Scale. Concordance and symmetry between partner's reports was assessed using the κ statistic and McNemar's test, respectively. Results: The sample included 915 partnered mothers and 698 partnered fathers of which 674 were couples. Over 85% of individuals perpetrated or were victims of verbal aggression. Perpetration and victimisation of physical IPV was reported by 37% and 28% of mothers and 11% and 8% of fathers, respectively. Fathers systematically under-reported IPV and significant differences emerged in the response distributions from couples with Tongan mothers compared with couples with Samoan or Cook Island Maori mothers. Discussion: IPV is common for many Pacific couples and consistent with that reported in other New Zealand groups. Mothers are as likely as fathers to perpetrate and be victims of this violence. However, patterns of reporting were different between mothers and fathers, and between Pacific ethnic groups, which has implications for the understanding and health promotion targeting of domestic violence.